THE EFFECT OF WORK SHIFT IMPLEMENTATION AND WORK MOTIVATION ON EMPLOYEE WORK PRODUCTIVITY AT PT SUMBER BINTANG REZEKI JIMBARAN SEMARANG REGENCY - Fau, Leoni Angela; Satato, Yuniarto R (Universitas Nusa Cendana, 2025)
This study examines the influence of work shift implementation and work motivation on employee productivity at PT Sumber Bintang Rezeki Jimbaran in Semarang Regency. Using a quantitative approach with an explanatory survey method, data were collected from 38 employees through a structured questionnaire. Multiple regression analysis revealed that both work shift implementation and work motivation individually had significant positive effects on employee productivity. The two variables collectively explained 67.9% of the variance in employee productivity. The findings highlighted that while both factors significantly influence productivity, work motivation demonstrated a slightly stronger effect. Analysis of demographic data showed a predominantly female (84.2%) and young workforce (60.5% aged 20-25 years), which may influence shift adaptation and motivational patterns. The study contributes practical implications for manufacturing companies in Indonesia seeking to optimize productivity through effectively designed shift systems and targeted motivational strategies tailored to specific workforce demographics. Keywords: Work Shift Implementation; Work Motivation; Employee Productivity; Manufacturing Industry; Indonesian Workforce